1998
DOI: 10.1002/(sici)1096-8644(1998)107:27+<137::aid-ajpa6>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of modern human origins: Geography, demography, and diversity in recent human evolution

Abstract: The origins of modern humans have been the central debate in palaeoanthropology during the last decade. We examine the problem in the context of the history of anthropology, the accumulating evidence for a recent African origin, and evolutionary mechanisms. Using a historical perspective, we show that the current controversy is a continuation of older conflicts and as such relates to questions of both origins and diversity. However, a better fossil sample, improved dates, and genetic data have introduced new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(27 citation statements)
references
References 126 publications
2
21
0
Order By: Relevance
“…Under this scenario, either the modern European–Neanderthal split time is very recent (i.e., ≤60 Kya) or the Neanderthal admixture proportion is extremely high (>>50%). Paleoanthropological evidence suggests that Neanderthals formed a distinct group of fossils at least 250 Kya [6,7], so the more recent modern European–Neanderthal split time is highly unlikely. In addition, most of the available evidence from paleoanthropology suggests that the Neanderthal contribution to the modern gene pool is limited [7], while previous Neanderthal mtDNA studies concluded that the Neanderthal contribution could be no more than 25% [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this scenario, either the modern European–Neanderthal split time is very recent (i.e., ≤60 Kya) or the Neanderthal admixture proportion is extremely high (>>50%). Paleoanthropological evidence suggests that Neanderthals formed a distinct group of fossils at least 250 Kya [6,7], so the more recent modern European–Neanderthal split time is highly unlikely. In addition, most of the available evidence from paleoanthropology suggests that the Neanderthal contribution to the modern gene pool is limited [7], while previous Neanderthal mtDNA studies concluded that the Neanderthal contribution could be no more than 25% [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Paleoanthropological evidence suggests that Neanderthals formed a distinct group of fossils at least 250 Kya [6,7], so the more recent modern European–Neanderthal split time is highly unlikely. In addition, most of the available evidence from paleoanthropology suggests that the Neanderthal contribution to the modern gene pool is limited [7], while previous Neanderthal mtDNA studies concluded that the Neanderthal contribution could be no more than 25% [8,9]. Furthermore, preliminary analyses of additional nuclear Neanderthal sequences suggest a much older human–Neanderthal sequence divergence time than was found by Green et al [10].…”
Section: Discussionmentioning
confidence: 99%
“…Even though AMH genetic diversity could have been impacted by cold periods ( Hewitt 2000 ; Arenas et al 2013 ), the specific genetic effect of the last glacial age that occurred between 13 and 29 Ka ( Straus 1991 ) has been little investigated. Similar to what happened with many other species during the last glacial maximum (LGM) ( Lahr and Foley 1998 ), modern humans might have retreated to refuge areas such as southern Europe as well as southern and south-eastern Asia ( Banks et al 2008 ; Stewart and Stringer 2012 ), and the extent of genetic differentiation between populations from different refugia might have increased during this period.…”
Section: Introductionmentioning
confidence: 88%
“…However, the number, the geographic origin and migratory routes and the timing of major dispersals remains elusive. For instance, there is evidence to support the origins of modern humans in eastern, central and southern Africa 18,3133 , single and multiple dispersals out of Africa 7,3436 , a north or south dispersal route 37,38 and estimates for the timing of dispersals occurring about 50 kyr–100 kyr ago 20,3943 . Three studies 4446 that leverage fresh, high-quality whole-genome sequencing data from geographically diverse individuals from more than 270 locations worldwide help to resolve some of these questions.…”
Section: Out Of Africa and The Meeting With Neanderthalsmentioning
confidence: 99%